Hubungan Rhinitis Alergi dengan Kejadian Asma Bronkial - M. Hadriyan Akbar Arief (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Allergic rhinitis defined as an inflammation on nasal mucosa which triggered by contact with allergen. Allergic rhinitis has been linked with bronchial asthma. For that reason, the relationship of allergic rhinitis with the incidence of bronchial asthma needs to be known in supporting the approach to diagnosis and treatment of one another. In this article a variety of literature studies are carried out to summarize and compare the results of the current understanding so that relevant publications are formed. The relationship between the two is explained pathophysiologically and epidemiologically. Pathophysiologically includes the effects of nasal physiology on the bronchus, nasobronchial reflexes, similar inflammation, and the mediators and markers involved. Epidemiologically, it is explained that rhinitis is a significant risk factor for the onset of asthma as an adult.